Protecting Our Migrant Workers from Violence: How the Legal Protection System Works? - Solekhah, Ragil Putri Amalia; Salsabila, Novita Intan ‘Aina (Law Research Review Quarterly, 2023)
There are many cases of violence against TKI, especially female immigrant workers. This analysis analyzes the legal protection for victims of violence, especially TKI. The method in this study uses a normative juridical study where the researcher uses several references as legal materials to analyze the topic of discussion. This case study finds that Law no. 39 of 2004 concerning the Placement and Protection of Indonesian Migrant Workers Abroad, is a regulation that regulates the protection of Indonesian migrant workers. This regulation stipulates that the regulation of TKI must be based on the principles of integration, equality of rights, democracy, social justice, gender justice and justice, anti-discrimination, and anti-trafficking. The government is responsible for enhancing efforts to protect Indonesian migrant workers abroad. For this reason, it is necessary to find an appropriate solution to overcome these problems and issues. This case study concludes that, although various legal theories and regulations are able to answer cases of violence against TKI, an in-depth analysis is needed to obtain a complete picture. This case study suggests that special regulations or laws are needed to prevent violence against women, in the sense of criminalizing criminal acts to providing legal remedies and sanctions for victims. In this case, sanctions are regulated not only against the perpetrators, but also the legal process and compensation, recovery and safety of victims.